1995
DOI: 10.1161/01.str.26.9.1558
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Spontaneous Intracerebral Hemorrhage

Abstract: Recent moderate and heavy alcohol intake as well as hypertension and likely also anticoagulant treatment seem to be independent risk factors for intracerebral hemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
86
1
9

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(105 citation statements)
references
References 41 publications
9
86
1
9
Order By: Relevance
“…This finding is consistent with the findings of previous case-control studies, which found recent heavy alcohol consumption to be a risk factor for ICH 23 and for ischemic stroke due to cardiogenic brain embolism 24 after controlling for hypertension. Heavy, chronic alcohol consumption is associated with cardiomyopathy, 25 which is known to predispose to cardiac arrhythmias and heart failure, both of which increase the risk for embolic stroke.…”
Section: Mechanismssupporting
confidence: 92%
“…This finding is consistent with the findings of previous case-control studies, which found recent heavy alcohol consumption to be a risk factor for ICH 23 and for ischemic stroke due to cardiogenic brain embolism 24 after controlling for hypertension. Heavy, chronic alcohol consumption is associated with cardiomyopathy, 25 which is known to predispose to cardiac arrhythmias and heart failure, both of which increase the risk for embolic stroke.…”
Section: Mechanismssupporting
confidence: 92%
“…113 The relative risk for SICH in hypertensive individuals, however, remains 3.9 to 13.3 times that for normotensive individuals. 20 Juvela and colleagues 62 have reported that recent moderate and heavy alcohol intake, hypertension, and anticoagulant treatment appear to be independent risk factors for SICH. Cigarette smoking seems to increase the risk for SAH, but is less strongly associated with SICH.…”
Section: Risk Factorsmentioning
confidence: 99%
“…1,2 On the other hand, liver cirrhosis is frequently associated with hematologic complications, especially thrombocytopenia and coagulation disorders. 3 The risk for development of ICH in patients with liver cirrhosis remains elusive.…”
mentioning
confidence: 99%